Treatment outcome and compliance to dose-intensified linac-based SBRT for unfavorable prostate tumors using a novel real-time organ-motion tracking - Raffaella Lucchini; Denis Panizza; Riccardo Ray Colciago; Veronica Vernier; Martina Camilla Daniotti; Valeria Faccenda; Stefano Arcangeli (Radiation Oncology, 2021)
Abstract Purpose/objectives To report preliminary data on treatment outcome and compliance to dose-intensified organ sparing SBRT for prostate cancer using a novel electromagnetic transmitter-based tracking system (RayPilotÒ System) to account for intra-fractional organ motion. Material/methods Thirteen patients with intermediate unfavorable (9) and selected high-risk (4) prostate cancer underwent dose-escalated SBRT in 4 or 5 fractions (BED1.5 = 279 Gy and 253 Gy, respectively). The VMAT treatment consisted in two 6FFF or 10FFF full arcs optimized to have the 95% isodose covering at least 95% of the PTV (2 mm isotropic expansion of the CTV). Whenever the real-time tracking registered a displacement that exceeded 2 mm during the setup and/or the beam delivery, the treatment was interrupted and the prostate motion was promptly corrected. The incidence of treatment-related genitourinary (GU) and gastrointestinal (GI) toxicity, patient QoL and PSA outcomes were computed from the start of treatment to the last follow-up date. Results All patients completed the treatment in the expected time (10.2 +/− 4.2 minutes) and their compliance to the procedure was excellent. No clinically significant acute Grade 2 or higher GI (rectal) and GU side effects were observed within 90 days from the treatment completion. The median IPSS increased from 8 at baseline to 12 one-month after treatment and settled to 6 at 3 months. EPIC-26 scores in the urinary domain decreased from a median baseline of 86 pre-treatment to 79 at one-month and returned to baseline at a later timepoint (median score of 85 at 3 months). EPIC-26 scores in the bowel domains did not show significant changes within 3 months following RT. The prostate was found within 1 mm from its initial position in 78% of the beam-on time, between 1 and 2 mm in 20%, and exceeded 2 mm only in 2%, after correction for motion which was performed in 45% of the fractions, either during setup or beam delivery. Conclusions Our preliminary findings show that dose intensified SBRT for unfavorable prostate tumors does not come at the cost of an increased toxicity, provided that a reliable technique for real time prostate monitoring is ensured. Fast FFF beams contributed to reduce intra-fractional motion. These observations need to be confirmed on a larger scale and a longer follow up.